1985
DOI: 10.1540/jsmr1965.21.95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soldium vanadate on the smooth muscle of the guinea-pig vas deferens.

Abstract: Sunano, S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Sodium vanadate at concentrations higher than 10-5 M induced tension development in the smooth muscle of guinea-pig vas deferens as reported in the preceding paper (Sunano et al, 1985). Tension developments were often (approximately half of preparations examined) associated with spontaneous contractions riding on elevated tension, especially when high concentrations of sodium vanadate (higher than 10-3 M) was used ( Fig.…”
Section: Effects Of Ca Removal On Vanadate-induced Tension Developmentsupporting
confidence: 71%
See 2 more Smart Citations
“…Sodium vanadate at concentrations higher than 10-5 M induced tension development in the smooth muscle of guinea-pig vas deferens as reported in the preceding paper (Sunano et al, 1985). Tension developments were often (approximately half of preparations examined) associated with spontaneous contractions riding on elevated tension, especially when high concentrations of sodium vanadate (higher than 10-3 M) was used ( Fig.…”
Section: Effects Of Ca Removal On Vanadate-induced Tension Developmentsupporting
confidence: 71%
“…It was demonstrated in the preceding paper that sodium vanadate acts directly on the smooth muscle of guinea-pig vas deferens and shows a slight depolarizing and spike-generating action (Sunano et al, 1985). Both depolarization and spike potential can induce contraction of smooth muscle of the vas deferens (Magaribuchi et al, 1971;Sunano, 1980;.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that sodium vanadate has contractile actions on smooth muscles of blood vessels (Ozaki and Urakawa, 1980;Rapp, 1981;Shimada et al, 1986), intestines (Hudgins and Bond, 1981;Ueda et al, 1982), air ways (Nayler and Sparrow, 1983), uterus (Grover et al, 1980;Mironneau et al, 1984), and was deferens (Garcia et al, 1981;Sunano et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that vanadate potently inhibits Na, K-ATPase of cell membranes in various muscles including uterine smooth muscle (Cantley et al, 1977;Akera et al, 1979;Grover et al, 1980;Vyskocil et al, 1981), the contractile effects have been thought to be independent of the inhibition of Na, K-ATPase for most smooth muscles (Ozaki and Urakawa, 1980;Rapp, 1981;Hudgins and Bond, 1981;Ueda et al, 1982;Nayler and Sparrow, 1983; Accepted for publication, June 12, 1987 Sunano et al, 1985;Shimada et al, 1986). In the smooth muscle of rat was deferens and rat uterus, however, the possibilities of involvement of Na, K-ATPase in the actions of vanadate have not been excluded (Grover et al, 1980;Garcia et al, 1981).…”
Section: Introductionmentioning
confidence: 99%